Surge in Economic Growth of Pakistan: A Case Study of China Pakistan Economic Corridor - Farooq, Maryam; Rao, Zia-ur-Rehman; Shoaib, Muhammad (Frontiers in Psychology, 2022)
China Pakistan Economic Corridor (CPEC) is considered a massive investment that can change the economic scenario of Pakistan. The purpose of the study is to examine the contribution to the economic growth of the sectors where CPEC is investing. This research uses time-series data for 31 years to investigate the impact of macro-economic variables like Foreign Direct Investment(FDI), Human Capital Investment (HCI), Transport Investment, and Information Communication Technology (ICT) on economic growth of Pakistan. The results of Fully Modified Ordinary Least Square Regression Specification show a positive nexus between FDI, HCI, and economic growth. While economic growth and information communication technology show a negative relationship. The results for the impact of transportation infrastructure on economic growth are statistically insignificant. This research suggests increasing the time period of the study to ascertain the implicit or explicit impact of CPEC on economic growth. The results also suggest the policymakers and researchers to focus on developing the human capital to reap the investment benefits of CPEC.